MODEL PEMBERITAAN INJIL MELALUI POLA DIALOG KEHIDUPAN SEHARI-HARI DITINJAU DARI YOHANES 4:4-42 - Kejar Hidup Laia (STT Saint Paul Bandung, 2021)
The conversation of Lord Jesus with the Samaritan woman as recorded in the Gospel of John 4:4-42 is one of the models of preaching the gospel with a daily life dialogue pattern. After conducted an investigation based on qualitative research methods with an exegesis study approach, the researcher confirmed that the model of preaching the gospel carried out by Jesus to the Samaritan woman was a model of living dialogue in the preaching of the gospel. This pattern of dialogue is a very effective model of preaching the Gospel in this age.